Optimization Of Surface Roughness Of Stainless Steel AISI 440 C Using Response Surface Methodology (RSM). (University of Thi-Qar Journal for Engineering Sciences, 2022)
Because of its high corrosion resistance and ability to preserve mechanical qualities at high temperatures, Stainless steels are used in a variety of applications, including automotive, aerospace, and marine. In metal turning, cutting speed, feed rate, and depth of cut are all essential machining parameters . The settings of these parameters determine the quality of the final turning results. The goal of this research is to see how changing these parameters affects the output factor (Surface Roughness). In addition, the behavior of stainless steel 440 C in dry turning conditions is being investigated for purpose to improve cutting conditions. In response surface methodology (RSM), the box-behnken design (BBD) technique is used, the surface roughness was modeled as a result to the parameters of cutting. The 17 trial runs were built using Design Expert (v12) to develop and test the empirical surface roughness mathematical model. The results indicated that the roughness is strongly affected by the feed rate, followed by cutting speed and depth of cut.